A Netnographic Study of Iranian Users’ Reactions to Dubbing Censorship in Instagram Posts - Ameri, Saeed; Ghodrati, Maryam (Journal of Audiovisual Translation, 2025)
Social online platforms offer a user-friendly venue for individuals to voice their opinions on virtually any topic, including dubbing. Naturally occurring data, such as Instagram comments, are valuable for their ecological validity, as they reflect authentic interactions beyond controlled settings. A few studies have leveraged such data to advance research on the reception of audiovisual translation. Adopting a netnographic approach, this study examines how Iranian viewers perceive censorship in Persian dubbing, as reflected in users’ comments on Instagram posts and sheds light on their reactions and perspectives concerning dubbing censorship in Iran. Findings show strong opposition among Iranian users to the censorship of dubbed content. Many users expressed that censorship distorts the storyline and narrative of the original product, resulting in a less immersive and enjoyable viewing experience. Nonetheless, some users acknowledged the potential benefits of censorship in certain contexts, such as foreign audiovisual content aimed at children and young adults, to safeguard their mental well-being. The paper underscores the need to reevaluate censorship policies in Persian dubbing. Lay summary When you sit down to watch the latest hit show or film with Persian dubbing on Channel 1 or one of the Iranian streaming services, you may notice some changes, such as different clothes on the characters, unusual ways of speaking, or awkward dialogue that doesn’t quite match the visuals. If so, you’ve likely faced censorship. This can be frustrating enough to make viewers stop watching the dubbed version and instead download the original film online with Persian subtitles, and of course, uncensored. But have you ever voiced your frustration with dubbing censorship on social media, like Instagram? This is what our study explores. We are interested in how Iranian Instagram users feel about censorship in Persian dubbing. Social media, especially Instagram, presents a space where people share their opinions openly, and these comments offer valuable insights beyond controlled experiments. By analyzing Instagram comments, we want to understand Iranians’ reactions to censorship in dubbing. Our findings show that most Iranian users strongly dislike censorship in dubbing. They feel it alters the original storyline and makes the viewing experience less enjoyable. But some people support limited censorship for children and teens, believing it helps protect their well-being. Overall, our study suggests it may be time to rethink censorship policies in Persian dubbing to better align with viewers’ preferences.